Induksi Kalus Pada Eksplan Batang Tanaman Binahong (Anredera cordifolia) Secara In Vitro Dengan Konsentrasi 2,4-DDan BAP Yang Berbeda - Widiyastuti, Linda Ochtivah, Triastuti Rahayu, S.Si., M.Si (2015)
Binahong is one of the plants that contain saponins, alkaloids, polyphenols, anthocyanins, flavonoids, oleanolic acid, protein, vitamin C.Binahong efficacious treatment of some diseases because they contain secondary metabolites such as ascorbic acid and flavonoids,diseases such as help treat wounds, typhoid, ulcers, colitis, hemorrhoids, swelling, blood clots, arthritis, bruises, gout, stroke and diabetes mellitus.The high secondary metabolites derived from callus culture in vitro.The purpose of this research to determine the effect of the concentration of 2,4-D and BAP on Binahong plant stem callus growth.The design of this research use 2 factorial completely randomized design (CRD):factor 1: the concentration of 2,4-D 0 ppm, 0.5 ppm, 1 ppm, 1.5 ppm (D) and factor 2: BAP concentration consisting of 0 ppm, 0.5 ppm (B). The parameters used are the speed of growth of callus, callus color, callus texture and size of callus.The results showed the concentration of 2,4-D 0.5 ppm and 0.5 ppm BAP is the most optimal concentration for callus growth rate and produce callus pure white with a compact texture.The concentration of 2,4-D 1.5 ppm and 0.5 ppm BAP produces white callus with crumb texture. The concentration of 2,4-D 1.5 ppm and 0.5 ppm BAP is the most optimal concentration for callus size.